Masticatory Function and Nutritional Status in Brazilian Institutionalized Elders: Influence of Denture Use - Rayssa Lucena Wanderley; Francisco Naldo Gomes Filho; Maryana Fernanda Rocha Bonifácio; Aldelany Ramalho Freire; Luiz Fabrício Santos de Oliveira; Mariana Marinho Davino de Medeiros; Renata Matheus Cunha Rodrigues Garcia; Yuri Wanderley Cavalcanti (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the influence of tooth loss and the use of removable dentures on chewing function and nutritional status of institutionalized elders. Material and Methods: Cross-sectional study with 155 elders from seven long-stay institutions in João Pessoa, Brazil. The participants were classified according to the presence of reminiscent teeth and use of dentures in four levels: toothless, without denture (1); toothless with a complete denture (2); partial toothless without denture (3) and partial toothless with a partial denture (4). Nutritional status was assessed using the Mini-Nutritional Assessment (MNA) instrument and the Body Mass Index (BMI). Swallowing threshold was used for the assessment of masticatory function, using a portion of roasted peanuts (3.7 g). Comparisons among groups were performed using Kruskal-Wallis test with Bonferroni adjustment, considering p<0.05. Results: MNA (p=0.702) and BMI (p=0.884) were not modified in relation to the presence of teeth and denture use. Toothless individuals without dentures had a lower swallowing threshold (p<0.001), whilst partial toothless with dentures had better masticatory function (p>0.05). Conclusion: The presence of reminiscent teeth and the use of dentures do not influence the nutritional status of the elders but interfere with the masticatory function. Prosthetic rehabilitation is desirable for complete toothless individuals.